Metalloantitubercular compounds part 3: synthesis, crystal structure, spectroscopy, electrochemistry and antimycobacterial activity of the copper(II) ciproploxacin (cfH) complex and its phenanthroline adduct - Saha, D. K.; Patitungkho, S.; Padhye, S.; Deobagkar, D. N.; Ozarkar, A.; Bhadbhade, Mohan M.; Gonnade, Rajesh G. (Transition Metal Chemistry, 2005)
The X-ray crystal structures of two ciprofloxacin compounds, viz. [Cu(cfH)(2)(Cl)(2)] (.) 2MeOH (.) 6H2O (2) and [Cu(cfH)(phen)Cl]BF4 (.) 4H(2)O (3) are reported. Complex ( 2) has a distorted octahedral geometry, whereas for the nitrogen adduct (3) a distorted square-pyramidal geometry is seen. Significant enhancement in the antimycobacterial activity of the copper conjugates correlates with their copper redox couples (Cu2+/Cu+) probably due to its relevance to intracellular accumulations and subsequent role in generating oxidative stress.

Molecular association via halogen bonding and other weak interactions in the crystal structures of 11-bromo-12-oxo-5 beta-cholan derivatives - Salunke, Deepak B.; Hazra, Braja G.; Gonnade, Rajesh G.; Pore, Vandana S.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Methyl 3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 2, methyl 11 alpha-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 3, methyl 11 beta-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 4 and methyl 11,11-dibromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 5 were synthesized. The crystal structures of these molecules were resolved to study the effect of bulky bromine atom in the steroid skeleton of cholic acid with different stereo-chemical orientations at C-11 on the two-dimensional arrangement of molecules and solid-state properties. All the molecules associate only via weak intermolecular interactions in their crystal structures, notable one being the Halogen Bonded assembly (C-Br center dot center dot center dot O) in 5. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 11-Bromosteroids; Cholic acid; crystal structure; Halogen bonding